Industrial espionage reality of the information age - Carlton, Stephen A.
Stephen A. Carlton discusses the procedures and methods by which managers can protect their valuable scientific and technical information
Here's what R&D managers can do in the face of an increasing need to protect their technical advantage.
The number of actual and attempted incidents of trade secret theft has increased significantly. In addition, competitive intelligence-gathering techniques have grown increasingly aggressive. Techniques used to acquire technical information are often bold and brazen, yet are frequently successful when used on unsuspecting employees. The more common techniques include : Posing as a fellow employee when requesting information over the telephone, posing as a student or professor at technical conferences, and sorting through trash containers. Research managers need to recognize the increased threat to their proprietary information and make sure that their employees are educated and motivated to protect valuable technical information.
Keywords: Information age; Industrial espionage